A Biomimetic Biphasic Osteochondral Scaffold with Layer‐Specific Release of Stem Cell Differentiation Inducers for the Reconstruction of Osteochondral Defects. Issue 23 (27th April 2020) - Liu, Xuemin; Wei, Yingqi; Xuan, Chengkai; Liu, Lei; Lai, Chen; Chai, Muyuan; Zhang, Zhaoguo; Wang, Lin; Shi, Xuetao
Abstract: There is a great challenge in regenerating osteochondral defects because they involve lesions of both cartilage and subchondral bone, which have remarkable differences in their chemical compositions and biological lineages. Thus, considering the complicated requirements in osteochondral reconstruction, a biomimetic biphasic osteochondral scaffold (BBOS) with the layer‐specific release of stem cell differentiation inducers are developed. The cartilage regeneration layer (cartilage scaffold, CS) in the BBOS contains a hyaluronic acid hydrogel to mimic the composition of cartilage, which is mechanically enhanced by host–guest supramolecular units to control the release of kartogenin (KGN). Additionally, a 3D‐printed hydroxyapatite (HAp) scaffold releasing alendronate (ALN) is employed as the bone‐regeneration layer (bone scaffold, BS). The two layers are bound by semi‐immersion and could regulate the hierarchical targeted differentiation behavior of the stem cells. Compared to the drug‐free scaffold, the MSCs in the BBOS could be promoted to differentiate into both chondrocytes and osteoblasts. The in vivo results demonstrate the strong promotion of cartilage or bone regeneration in their respective layers. It is expected that this BBOS with layer‐specific inducer release can become a new strategy for osteochondral regeneration. Abstract : Herein, a semi‐embedded biomimetic biphasic osteochondral scaffold with layer‐specific release of stem cell differentiation inducers is developed. It contains a hydrogel‐based cartilage‐regeneration layer that releases kartogenin and a 3D‐printed bone regeneration layer that releases alendronate. This novel scaffold can promote cartilage or bone regeneration in the respective layers and is expected to be a new strategy for osteochondral regeneration.